The fast and the furious: Ultrafast hot electrons in plasmonic metastructures. Size and structure matter. (August 2019) - Besteiro, Lucas V.; Yu, Peng; Wang, Zhiming; Holleitner, Alexander W.; Hartland, Gregory V.; Wiederrecht, Gary P.; Govorov, Alexander O.
Graphical abstract: Highlights: Special geometries generate larger numbers of plasmonic, high-energy "hot" electrons. Metasurfaces with hot spots and infrared gap plasmons show anomalous ultrafast responses due to non-thermalized hot carriers. Quantum two-temperature model describes the dynamics of generation of hot electrons. The photoemission of plasmonic electrons facilitates ultrafast electronics. Nanocrystals exhibit coherent phonon oscillations after pulse excitation. Abstract: This review focuses on the generation of energetic (hot) electrons in plasmonic metastructures and nanomaterials, and their characterization through time-resolved spectroscopy. Excitation of hot electrons under illumination occurs in any metal or conductor, but their number will vary for each type of nanostructure. While plasmonic resonances are well described classically, the excitation of hot electrons (HEs) is a quantum process and its description requires further elaboration. Some potential applications for HEs lie in the fields of photo-catalysis and optoelectronics, and their study constitutes a very active interdisciplinary research direction that involves chemistry, physics and device engineering. Here we focus on some particular developments enabling the use of hot carriers for these applications. Particularly, we discuss the approaches and structures required to create hot carriers, the temporal dynamics of hot carrier formation and relaxation, and relevant theoretical methods used to compute the HE dynamics. The observations presented here support the conclusion that the shape of the nanostructure matters. Although metastructures with infrared gap plasmons can exhibit spatially extended hot spots and anomalously large numbers of non-thermalized HEs, most excited carriers in a plasmonic nanostructure typically have small excitation energies. Here we discuss ways to strongly increase the number of high-energy electrons, highlighting the role of hot spots, system size, geometry and resonant frequencies. To generate HEs efficiently, we can take advantage of special geometries with hot spots, such as metamaterial absorbers with ultra-narrow gaps or nanostars. Furthermore, we discuss the applications in ultrafast electronics based on plasmon-enhanced photoemission and tunneling in the nonlinear regime. Considering the longer timescale phenomena, we also present studies on the coherent dynamics in a nanostructure after electron thermalization, showing acoustic breathing modes. In this paper, we review some key developments in the field of ultra-fast plasmonic dynamics and provide a perspective for its possible next steps.